IMPACT OF ULTRAVIOLET RADIATION ON BACTERIAL GROWTH OF KN95 MASK - Ni Made Amelia Ratnata Dewi; Eustachius Hagni Wardoyo; Candra Eka Puspitasari; Raisya Hasina (Universitas Muhammadiyah Ponorogo, 2021)
Pandemic SARS CoV-2 is currently spreading around the world. Preventive measures to be implemented include using Personal Protective Equipment (PPE) especially mask which lead to a lack of mask supply. Strategy is proposed by decontaminating it so that it can be used repeatedly. This research was conducted to compare the effectiveness of UV radiation disinfection in different duration on the KN95 mask. This research was conducted by decontaminating of KN95 mask using UV radiation with radiation time of 15, 30, and 45 minutes. The mask was swab before and after the radiation. Examination for the growth of pathogen bacterial colonies and total plate count method was done to determine the effectivity. It was found the number of germs before and after has decreased significantly radiation at 30 (P = 0.036) and 45 minutes (P = 0.037). It also can be effective in decontaminating pathogen bacterial as the number colony of Staphylococcus aureus has decreased significantly in 30 minutes (P=0.034) and 45 minutes exposure (P= 0.037). The results of this study indicate that UV radiation for 30 and 45 minutes can be effective in decontaminating pathogen bacterial